(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
During the operation of several equipments, there are lots of failure cases in mechanical components subjected to multiaxial stress, where among them stands out the fatigue phenomenon. In this context, this paper presents the failure mode as a life prediction model for multiaxial fatigue through numerical analysis using the finite element method, assessing in which situations, the equivalent stress-based models for static loads can also be used on estimating the multiaxial fatigue life with alternating loads. It will also be assessed the accuracy in which the approximation polynomial order of the element used for discretization has on the results. The literature review of this work addresses the definitions of stress states, alternating loads history, yield function models and later the life prediction for multiaxial fatigue. Given these definitions, the work focuses on performing a numerical simulation for a model submitted to torsion and alternating tensile stresses. To validate the stress results obtained by computer simulation, experimental tests have been performed on prototypes by electrical extensometer. Then, using the signaled von Mises model, it will be discussed the influence that the used elements have on the multiaxial fatigue life results obtained through commercial software of multiphysics analysis Ansys®.